2011
DOI: 10.1080/1369183x.2011.623618
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identity and Agency in Migration Decision-Making: Evidence from Vietnam

Abstract: This paper examines the influences of gender as an identity on an individual's ability to exercise agency in decision-making about internal migration in Vietnam. Women and men exert agency with reference to prevailing social norms in order to negotiate for or against their own migration and that of others. It has been well recognised that, beyond sex, their specific gender identity as mothers or fathers, daughters or sons, husbands or wives, etc. impacts on who can migrate for what kind of work. However, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 17 publications
2
68
2
5
Order By: Relevance
“…This finding is consistent with the previous studies that have suggested that men exercise more power and authority than women in migrant decision-making due to the prevailing patriarchal norms of their society (Chant, 1998;Grasmuck & Pessar, 1991;Hoang, 2011).…”
Section: Men As Decision Makerssupporting
confidence: 83%
“…This finding is consistent with the previous studies that have suggested that men exercise more power and authority than women in migrant decision-making due to the prevailing patriarchal norms of their society (Chant, 1998;Grasmuck & Pessar, 1991;Hoang, 2011).…”
Section: Men As Decision Makerssupporting
confidence: 83%
“…The prospect of upward economic mobility for the family down the road requires immediate downward social mobility on the part of the migrant woman for whom breadwinning is traditionally not a primary duty (see also Hirsch 2003;Hoang and Yeoh 2011). As such, only certain women in certain circumstances are prepared to take on that challenge (Hoang 2011(Hoang , 1448.…”
Section: Resultsmentioning
confidence: 99%
“…Hoang and Yeoh 2011) but also sparks concerns about the 'corruptive' effects of migration on women's morals. Men who let their wives migrate, as Hoang (2011Hoang ( , 1447 observes elsewhere in Northern Vietnam, tend to be seen (by their male peers) as 'losers'. Migrant infidelity is considered inevitable.…”
Section: Money and Infidelity In Sexual-affective Economies Of Migrationmentioning
confidence: 99%
“…The problem is that household theories of migration consider a household to be composed of actors with equal power and agreed aims, though this is quite often not the case, especially in cultures where women have less power than men in the family decisionmaking (de Haas & Fokkema, 2010;Gubhaju & De Jong, 2009;Hoang, 2011;Stecklov, Carletto, Azzarri, & Davis, 2010).…”
Section: Social Context In Migrationmentioning
confidence: 99%